2003
DOI: 10.1191/0269215503cr581oa
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary controlled study to determine whether whole-plant cannabis extracts can improve intractable neurogenic symptoms

Abstract: Cannabis medicinal extracts can improve neurogenic symptoms unresponsive to standard treatments. Unwanted effects are predictable and generally well tolerated. Larger scale studies are warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
2
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(290 citation statements)
references
References 18 publications
7
270
2
9
Order By: Relevance
“…84,86 Hagenbach et al 70 , showed that THC may have some analgesic properties to help SCI patients with spasticity related pain. Wade et al 87 conducted an RCT of sublingual 2.5 mg THC and/or cannabidiol and found that it significantly reduced pain, muscle spasm, spasticity and sleep difficulties in a group consisting largely of multiple sclerosis patients with neuropathic pain. Unfortunately, only a small number of the patients in this study had a SCI, so it did not meet our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…84,86 Hagenbach et al 70 , showed that THC may have some analgesic properties to help SCI patients with spasticity related pain. Wade et al 87 conducted an RCT of sublingual 2.5 mg THC and/or cannabidiol and found that it significantly reduced pain, muscle spasm, spasticity and sleep difficulties in a group consisting largely of multiple sclerosis patients with neuropathic pain. Unfortunately, only a small number of the patients in this study had a SCI, so it did not meet our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain may be an important indication for the treatment with THC and cannabis. There are several reports of pain reduction in MS by THC 19,41,42 and cannabis, 38,19 in central neuropathic pain from brachial plexus avulsion 43 and in neuropathic pain in HIV positives. 44 However, Attal et al 45 were not able to confirm the efficacy of THC in chronic refractory neuropathic pain in an open study with eight patients who received daily doses of up to 25 mg dronabinol.…”
Section: Discussionmentioning
confidence: 99%
“…The putative beneficial effects of combined THC and CBD also have been investigated recently in several clinical trials for multiple sclerosis, neuropathic pain, and varied neurogenic symptoms (Berman et al, 2004;Brady et al, 2004;Rog et al, 2005;Wade et al, 2004;Wade et al, 2003). In addition, Sativex®, a 1:1 THC: CBD ratio oromucosal spray formulation, is currently marketed in Canada for treatment of neuropathic pain associated with multiple sclerosis.…”
Section: Preclinical and Clinical Interactions Between Thc And Cbdmentioning
confidence: 99%